Urbanization has opposite effects on the territory size of two passerine birds - Juárez Jovel, Roselvy (2020)
Background: Urban expansion has been identified as one of the leading drivers of biodiversity change or loss. For birds, urbanization is specifically related to survival, breeding success, and territory size. Understanding how different birds adjust territory size in response to urbanization is essential for their conservation in urban environments and to better understand why some species are lost and others persist under this condition. We evaluated the effect of urbanization on the territory size of an urban avoider species, White-eared Ground-Sparrow (Melozone leucotis), and an urban adapter species, House Wren (Troglodytes aedon), at five Costa Rican sites. Methods: We measured the size of 30 ground-sparrow and 28 wren territories using a total of 296 h of observation. We followed each individual for at least 1 h per day for at least 2 days of two consecutive years, and geo-referenced their locations. Territory size was estimated using the minimum convex polygon method. We measured the urban surfaces (roads, buildings, any other paved area, soccer fields, lawns, and gardens with short grass) within territories. Results: Ground-sparrow territories were larger at the highly urbanized site than at the non-urbanized site. Wren territories were larger at the low urbanized site than at the highly urbanized site. We found a positive relationship between urban surface and territory size for the ground-sparrow, but not for the wren. Conclusions: Our results showed that not all birds adjust territory size in the same way in response to urbanization. We showed that urban avoiders probably need to defend larger territories in urban environments to find all the resources required to survive because urban environments may provide insufficient resources such as food or shelter. Urban adapters on the other hand defend smaller territories in urban environments because even small territories may provide sufficient resources. These results suggest specific behavioral adaptations developed by Neotropical birds inhabiting urban environments.